Pengaruh Literasi Ekonomi Terhadap Persepsi Kesetaraan Gender Pada Mahasiswa Pendidikan Ekonomi Uhamka - Susanti, Eka Nana; Suswandari, Suswandari; Putri, Erika (Universitas Hamzanwadi, 2024)
The phenomenon of gender inequality is one of the causes of a country's economic growth problems. Developed countries are characterized by high levels of economic growth or economic complexity. One of the efforts made by developed countries is to increase investment in education equally for men and women. However, developing countries have not been able to achieve this because of limited opportunities for women in terms of education and employment. The level of education is a sign that there are differences in literacy according to the level of education. There is research that states that economic growth through women's empowerment is supported by education and literacy levels, but there is research that says education has no effect on gender equality. Therefore, the aim of this research is to determine the effect of economic literacy on perceptions of gender equality among students majoring in Economic Education at UHAMKA using quantitative research methods. The research population was students majoring in economics education at UHAMKA. Data collection methods are questionnaires and interviews. The research results show that economic literacy influences perceptions of gender equality. The magnitude of the influence of economic literacy on perceptions of gender equality is 21.40%.